Implementing Multimodal Hardware Security with 2D α‐In2Se3 Ferroelectric Transistor - Xinwei Zhang; Jiachao Zhou; Yishu Zhang; Jian Chai; Yongqing Bai; Hailiang Wang; Qian He; Xi Wang; Lin Wang; Yuda Zhao; Yang Xu; Bin Yu (Advanced Science)
Abstract Security is a critical challenge in the integrated circuit (IC) industry, yet device‐level hardware security remains largely underexplored. Most existing solutions necessitate modifications to current technology nodes and typically address only a single security threat, leaving them vulnerable to diverse attacks while incurring substantial costs in area, energy, and resources. In this study, an out‐of‐the‐box security solution is proposed that integrates an in‐memory sensing and computing (IMSC) architecture based on α‐In2Se3 transistor, specifically designed for versatile and multimodal secure applications. By leveraging the unique ferroelectric, optoelectronic, and semiconducting properties of α‐In2Se3, the study demonstrates the secure transistor's electronic and optoelectronic synaptic behaviors, along with its capability for reconfigurable logic operations. Based on these, the secure transistor successfully implements four key security primitives: anticounterfeiting, watermarking, logic locking, and IC camouflaging in a single‐transistor structure, offering robust protection against counterfeit ICs, intellectual property theft, and reverse engineering. The multimodal secure transistor demonstrates the functional flexibility in addressing various security threats.